THE EFFECTS OF COOPERATIVE LEARNING METHOD AND LEARNING MOTIVATION: IMPROVING READING COMPREHENSION - Hayani; Tahrun; Mulyadi (Esteem Journal of English Education Study Programme, 2025)
The purpose of this study was to look into how eighth-grade students at MTs. Negeri 2 Ogan Komering Ilir's cooperative learning and learning motivation strategies affected their reading comprehension skills. The study investigated the effects of two independent variables—methods and learning motivation—using a 2x2 factorial design (with two levels: high motivation and low motivation). Four different groups were created out of the participants: class without treatment-low motivation, class without treatment-high motivation, cooperative learning-low motivation, and cooperative learning-high motivation. Tests and questionnaires were used to gather information about the participants' reading comprehension abilities. The results showed that students with varying levels of learning desire, as well as those who participated in cooperative learning and attended class without receiving any instruction, had differing reading comprehension abilities. Nevertheless, it was not discovered that there was a statistically significant interaction between cooperative learning and learning motivation. These findings imply that although learning motivation and cooperative learning both have an independent impact on reading comprehension, their combined effect could not have a substantial effect on students' performance in this specific situation. The results advance our knowledge of how technique and student motivation interact to improve reading comprehension abilities.